Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. Urbanism in the City of Salé: its Patterns and Factors Dr. Nezha Arabi, Dr. Mohamed Aneflouss 2. The role of electronic news websites in enhancing national identity among university students at the University of Jordan (2011-2015) Mr. Hamza Khalaf Abu Rumman 3. Means of calling the Messengers: An analytical study of the calling of the Prophet of God, Abraham, peace be upon him Ms. Haila Ali Mohammed Al-Ahmari, Co-Prof. Ahmed Ali Mohammed Al-Zamli 4. The Schooling Situation of Special Categories in the Education and Training System, Taza Province – Morocco Mr. Abdelilah El-Alami , Dr. Jaouad El-Bazoui , Dr. Abdelouahed Bouberria 5. Netflix Platform Binge Watching and its Relationship to Narrative Transportation Among Saudi Youth Ms. Amal Ali Mahnabi, Prof. Shua’a Abdulrahman Aljasir 6. Sports violence associated with football matches, a case study of Houari Abu Madian Stadium in Palestine - Case Study Mr. Salem Kh. Nassr